2017
DOI: 10.1038/mp.2017.55
|View full text |Cite
|
Sign up to set email alerts
|

The nucleus reuniens: a key node in the neurocircuitry of stress and depression

Abstract: The hippocampus and prefrontal cortex (PFC) are connected in a reciprocal manner: whereas the hippocampus projects directly to the PFC, a polysynaptic pathway that passes through the nucleus reuniens (RE) of the thalamus relays inputs from the PFC to the hippocampus. The present study demonstrates that lesioning and/or inactivation of the RE reduces coherence in the PFC–hippocampal pathway, provokes an antidepressant-like behavioral response in the forced swim test and prevents, but does not ameliorate, anhedo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 59 publications
2
35
0
3
Order By: Relevance
“…Within this circuit, the dorsal hippocampus performs primarily cognitive functions, while the ventral relates to emotional behavior (Fanselow & Dong, 2010). Moreover, synchrony between oscillations of hippocampal dorsal or ventral subregions, and PFC has been related respectively to cognitive (O'Neill et al, 2013) and emotional behavior (Adhikari, Topiwala, & Gordon, 2010;Kafetzopoulos et al, 2017;Mateus-Pinheiro et al, 2016;Oliveira et al, 2013). Specifically, and despite the indirect connections, O'Neill and colleagues demonstrated that dHIP theta oscillations are synchronized with theta oscillations in the mPFC, and that theta synchrony is critical for a spatial memory task.…”
Section: Discussionmentioning
confidence: 99%
“…Within this circuit, the dorsal hippocampus performs primarily cognitive functions, while the ventral relates to emotional behavior (Fanselow & Dong, 2010). Moreover, synchrony between oscillations of hippocampal dorsal or ventral subregions, and PFC has been related respectively to cognitive (O'Neill et al, 2013) and emotional behavior (Adhikari, Topiwala, & Gordon, 2010;Kafetzopoulos et al, 2017;Mateus-Pinheiro et al, 2016;Oliveira et al, 2013). Specifically, and despite the indirect connections, O'Neill and colleagues demonstrated that dHIP theta oscillations are synchronized with theta oscillations in the mPFC, and that theta synchrony is critical for a spatial memory task.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, lidocaine inactivation of RE resulted in a decreased coherence between 2-5 Hz delta oscillations in mPFC (PL) and HC, but had minimal effect on coupling at theta frequencies (Roy et al 2017). On the other hand, an N-methyl-D-aspartate (NMDA) lesion of RE impaired the coherence of mPFC-HC (PL-CA1) theta (and beta) frequency oscillations (Kafetzopoulos et al 2018). Interregional synchronization in the dorsal CA1-RE-mPFC direction was also observed.…”
Section: Role Of Re In Oscillations and Synchronizationmentioning
confidence: 99%
“…Due, in part, to its key position in between the HC and mPFC, RE dysfunction may lead to major clinical problems, such as persistent working memory impairments and other types of cognitive dysfunction shared by many neuropsychiatric disorders (Meyer-Lindenberg et al 2001Lawrie et al 2002;Bassett et al 2012;Venkataraman et al 2012;Argyelan et al 2014). Although little is known about RE dysfunction, to date, RE has been suggested to be involved in Alzheimer's disease (Braak and Braak 1991;Moretti et al 2011;Hardenacke et al 2013), Korsakoff's syndrome (Visser et al 1999), autism (Ray et al 2005), stress and depression (Kafetzopoulos et al 2018), epilepsy (Hirayasu and Wada 1992;Bertram et al 2001;Graef et al 2009;Sloan and Bertram 2009;Wang et al 2009;Drexel et al 2011), and schizophrenia (Cohen et al 1998;Lambe et al 2007;Lisman et al 2010;Sigurdson et al 2010;Lisman 2012;Zhang et al 2012;Saalman 2014;Duan et al 2015). In Alzheimer's disease, there is a highly specific pattern of neurofibrillary tangles in RE, a pattern that was consistently restricted to those patients with the most severe symptoms (Braak and Braak 1991).…”
Section: Clinical Relevance Of Re Dysfunctionmentioning
confidence: 99%
“…It was shown recently (Kafetzopoulos et al 2017) in freely moving rats that nRE lesion reduced PFC–HC coherence without affecting PFC and HC LFP power, and had anti-depressive effects, as measured in the forced swim test and the chronic mild stress model of depressive behavior in rodents. It was thus proposed that reduced PFC–HC coherence was an important factor contributing to nRE’s impact on the overall brain connectome in chronic stress, along with other factors including stress-induced deficits of neuroplasticity, such as dendritic atrophy and spine loss in the PFC (Kafetzopoulos et al 2017). Regardless of mechanism, given the selective and task-dependent entrainment of PFC ensemble activity to RR, the simultaneous selective enhancement of RROs in HC by nRE may mediate task-dependent information flow from PFC to HC.…”
Section: Dear Editormentioning
confidence: 98%